Superstar - Davis, Mandy (Harper, an imprint of HarperCollins Publishers, 2017)
Lester's first days as a fifth grader at Quarry Elementary School are not even a little bit like he thought they would be -- the cafeteria is too loud for Lester's ears, there are too many kids, and then there's the bully. Lester was always home-schooled, and now he's shocked to be stuck in a school where everything just seems wrong. That's until he hears about the science fair, which goes really well for Lester! But then things go a bit sideways, and Lester has to find his way back. A touching peek into the life of a sensitive autism-spectrum boy facing the everydayness of elementary school, Superstar testifies that what you can do isn't nearly as important as who you are.